Metformin as targeted treatment in fragile X syndrome. Issue 2 (25th September 2017) - Dy, A.B.C.; Tassone, F.; Eldeeb, M.; Salcedo‐Arellano, M.J.; Tartaglia, N.; Hagerman, R.
Abstract : Background: Individuals with fragile X syndrome (FXS) have both behavioral and medical comorbidities and the latter include obesity in approximately 30% and the Prader‐Willi Phenotype (PWP) characterized by severe hyperphagia and morbid obesity in less than 10%. Metformin is a drug used in individuals with type 2 diabetes, obesity or impaired glucose tolerance and it has a strong safety profile in children and adults. Recently published studies in the Drosophila model and the knock out mouse model of FXS treated with metformin demonstrate the rescue of multiple phenotypes of FXS. Materials and Methods: We present 7 cases of individuals with FXS who have been treated with metformin clinically. One case with type 2 diabetes, 3 cases with the PWP, 2 adults with obesity and/or behavioral problems and, a young child with FXS. These individuals were clinically treated with metformin and monitored for behavioral changes with the Aberrant Behavior Checklist and metabolic changes with a fasting glucose and HgbA1c. Results: We found consistent improvements in irritability, social responsiveness, hyperactivity, and social avoidance, in addition to comments from the family regarding improvements in language and conversational skills. No significant side‐effects were noted and most patients with obesity lost weight. Conclusion: We recommend a controlled trial of metformin in those with FXS. Metformin appears to be an effective treatment of obesity including those with the PWP in FXS. Our study suggests that metformin may also be a targeted treatment for improving behavior and language in children and adults with FXS. Abstract :